Dividend Policy Adaptation Strategies of New Issuers toward Capital Market Expectations: A Phenomenological Study - Sandopart, Dewa Putu Yohanes Agata L. (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
This study aims to explore the dividend policy adaptation strategies employed by new issuers in responding to capital market expectations following an initial public offering (IPO). Using an interpretative phenomenological approach, this study involved 12 informants from 8 companies that conducted IPOs on the Indonesia Stock Exchange during the 2021–2023 period. Data were collected through semi-structured in-depth interviews, document analysis, and field notes. Data analysis followed the six-stage Interpretative Phenomenological Analysis (IPA) method. The findings identified four superordinate themes: signaling conformity (adherence to market signals), reported by 83.3% of informants; dividend smoothing, confirmed by all informants (100%); strategic decoupling (separation of formal policy from actual practice), identified in 58.3% of informants; and dividend theater (dividend narration as symbolic performance), which represents the original contribution of this study. The analysis reveals that the dividend policy of new issuers is not merely a rational financial decision but rather a social phenomenon shaped by collective market expectations and institutional legitimacy pressures. This study enriches signaling theory, agency theory, and institutional theory by incorporating processual and contextual dimensions. Policy implications recommend strengthening the Financial Services Authority’s oversight of earnings management practices and mandating new issuers to present more realistic dividend projections in their prospectuses.